Left atrial function after standalone totally thoracoscopic left atrial appendage exclusion in atrial fibrillation patients with absolute contraindication to oral anticoagulation therapy - Marini, Massimiliano; Pannone, Luigi; Branzoli, Stefano; Tedoldi, Francesca; D’Onghia, Giovanni; Fanti, Diego; Sarao, Emanuele; Guarracini, Fabrizio; Quintarelli, Silvia; Monaco, Cinzia; Graffigna, Angelo; Bonmassari, Roberto; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Left atrial appendage (LAA) is the most common source of thrombi in patients with atrial fibrillation (AF). The Totally Thoracoscopic (TT)-LAA exclusion with epicardial clip is a safe and effective procedure, but the effect on left atrial (LA) function remains unknown. The aim of this study was to assess the effect of TT-LAA exclusion on LA function. Methods: 26 patients with AF and contraindication to oral anticoagulation (OAC) underwent standalone TT-LAA exclusion with the clip device. All patients were screened preoperatively with 3D CT scan, trans-esophageal echocardiography, spirometry and cerebrovascular doppler ultrasound. Intraoperative clip positioning and LAA exclusion were guided and confirmed by trans-esophageal echo. To evaluate LA function, standard transthoracic echocardiography and 2D strain of LA were performed before surgery, at discharge and at 3-month follow-up. Results: The mean CHA2DS2-VASc and HASBLED scores were 4.6 and 2.4 respectively. There were no major complications during the procedure. At median follow-up of 10.3 months, 1 (3.8%) non cardiovascular death, 1 (3.8%) stroke and 4 (15.4%) cardiovascular hospitalizations occurred. At 2D strain of LA, the reservoir function decreased significantly at discharge, compared to baseline and recovered at 3-months follow-up. Furthermore, NT-proBNP increased significantly after the procedure with a return to baseline after 3 months. Changes in E/A were persistent at three months. Conclusions: TT-LAA exclusion with clip device is a safe and effective procedure in preventing AF related stroke in patients with contraindication to OAC. LAA epicardial clip might impair the LA reservoir function with a recovery over time.